DERIVING INHERENT OPTICAL PROPERTIES FROM MERIS IMAGERY AND IN SITU MEASUREMENT USING QUASI-ANALYTICAL ALGORITHM - Wiwin Ambarwulan; Widiatmaka; Syarif Budhiman (BRIN, 2013)
The paper describes inherent optical properties (IOP) of the Berau coastal waters derived from in situ measurements and Medium Resolution Imaging Spectrometer (MERIS) satellite data. Field measurements of optical water, total suspended matter (TSM), and chlorophyll-a (Chl-a) concentrations were carried out during the dry season of 2007. During this periode, only four MERISdata were coincided with in situ measurements on 31 August 2007. The MERIS top-of-atmosphere radiances were atmospherically corrected using the MODTRAN radiative transfer model. The in situ optical measurement have been processed into apparent optical properties (AOP) and sub surface irradiance. The remote sensing reflectance of in situ measurement as well as MERIS data were inverted into the IOP using quasi-analytical algorithm (QAA). The result indicated that coefficient of determination (R 2) of backscattering coefficients of suspended particles (bbp) increased with increasing wavelength, however the R2 of absorption spectra of phytoplankton (aph) decreased with increasing wavelength.